Examining the Challenges Facing Implementation of Government Programs on Poverty Eradication: A Case Study of Youth Livelihood Programme in Northern Division. - Nyamwiza, Lydia (Kabale University, 2023)
Poverty is a harsh and undesired phenomenon in mankind that needs to be reduced and if possible eradicating it is unquestionable. Eradicating poverty in Uganda is an ethical, social, political, and economic imperative of all mankind in Uganda that has called on the government to address the root causes of poverty by providing the basic needs for all and ensuring that the poor have access to productive resources, including credit, and education. This is done through improving access to sustainable livelihoods, entrepreneurial opportunities, and productive resources; providing universal access to basic social services and progressively developing social protection systems to support those who cannot support themselves. The researcher examined the challenges facing the implementation of government poverty eradication programs. A case study of the youth livelihood programme in the northern division